Territorial Management in the Amazon from the Perspective of Ecological Economics: Proposition of a Conceptual Model - Lima Júnior, Francisco Bezerra; Costa, Carlos Alberto Franco da; Maciel, Raimundo Cláudio Gomes; Soliani, Rodrigo Duarte (Fronteira: Journal of Social, Technological and Environmental Science, 2026)
The Amazon region faces intense ecological and sociopolitical pressures resulting from a development model based on the intensive exploitation of natural resources and unidimensional economic metrics. In this context, it is necessary to develop analytical instruments compatible with the complexity of the region’s socioecological systems. This article proposes a conceptual model of ecological territorial management for the Amazon, grounded in the principles of Ecological Economics and operationalized through the Multicriteria Sustainability Index (MSI). The methodology consisted of a systematic literature review covering studies published between 2020 and 2025 on territorial management, multicriteria methods, and sustainability in Amazonian contexts. The analysis of 51 articles allowed the identification of three core analytical categories: normative values, sustainability dimensions, and substantive criteria. As the main result, the paper presents a model structured into five dimensions—environmental, social, economic, governance, and sustainable productive practices—articulated with substantive criteria and normative values such as environmental justice, equity, and ecological metabolism. The MSI was selected as the operational axis due to its methodological flexibility, territorial adaptability, and participatory validation processes. The results indicate that the model constitutes an analytical alternative applicable to territorial planning in complex regions such as the Amazon. Its implementation, however, requires institutional capacity, availability of local data, and qualified participatory processes. Future research should explore its empirical application and compare it with other multicriteria approaches to assess its effectiveness in formulating territorially sensitive public policies.